Unilateral Adrenal Hyperplasia: A Rare Cause of Primary Aldosteronism - Mahno, Noor Ezmas; Rohaizak, M.; Nordashima, AS.; Yazmin, Y. (IIUM Medical Journal Malaysia, 2021)
A 73-year-old gentleman with a background history of long-standing hypertension and hyperlipidaemia presented with one-year history of persistent asymptomatic hypokalaemia associated with metabolic alkalosis. Within a few months, the hypertension worsened, needing increasing dose of anti-hypertensive agents. Biochemical test showed an elevated aldosterone-renin ratio but the computerized tomography (CT) scan of adrenal did not show any adrenal mass. Arterial stimulation venous sampling (ASVS) lateralized the lesion to the left side. A left retroperitoneal adrenalectomy was performed with immediate reversal of hypokalaemia and improvement of blood pressure control to only single anti-hypertensive agent.